KEPEMIMPINAN PEMUDA PADA ORGANISASI RUMAH INSPIRASI KALIMANTAN TIMUR DALAM MENINGKATKAN MOTIVASI GENERASI MUDA KALIMANTAN TIMUR PERIODE TAHUN 2016 – 2020 - Fitriani Fitriani (Jurnal Paradigma (JP), 2021)
This study aims and focuses on describing, analyzing, and interpreting youth leadership, knowing the methods applied and the factors inhibiting and supporting youth leadership in the East Kalimantan Rumah Inspirasi organization in increasing the motivation of East Kalimantan young people in the period of 2016 - 2020. Using the approach descriptive qualitative with data collection techniques based on in-depth interviews, observation, and documentation and subsequently testing the data's validity using triangulation data validity techniques. The findings of this study are that the leadership of the Executive Director / CEO of the democratic in East Kalimantan Rumah Inspirasi proved to be able to inspire and motivate the younger generation. Keywords: youth, leadership, organization, rumah inspirasi,  motivation